Bricolage approach in social impact measurement of social enterprises in Vietnam - Doan, Thanh Hai (Université Saint-Paul / Saint Paul University, 2022)
Social impact measurement (SIM) plays a significant role in showing the contribution and accountability of social enterprises to society. Although there are many SIM methods available in the literature, most social enterprises, especially small and medium social enterprises in resource-constraint contexts, did not measure impact. Bricolage was explored in literature as an efficient approach in such constraints. However, there is still an ambiguity on how social enterprises use the bricolage approach in social impact measurement. Particularly in a developing economy like Vietnam, where the social enterprise sector is growing fast, literature on social impact measurement of social enterprises is also under-researched. There is still a shortage of studies focusing on the bricolage approach in social impact measurement and the motivations and challenges behind this SIM practice, which becomes the goal of this study. Exploring social impact measurement in three aspects: the motivations, the challenges, and the approaches in social impact measurement, this study uses three theoretical lenses respectively: (1) Intrinsic and Extrinsic motivations in social entrepreneurship; (2) The delegitimization model of formal methods in social impact measurement and (3) Bricolage approach in social impact measurement. This qualitative research involved three case studies of well-established social enterprises measuring impact regularly, representing three hybrid models in the social enterprise spectrum (mission-driven, market-driven, and mixed motives). Data was collected through nine in-depth interviews with ten people, document analysis, and researcher observations. This research enriches the knowledge of the social impact measurement in developing countries such as Vietnam in three interrelated aspects. First, it advances motivations theories by a) pointing out that extrinsic motivations have a dominant position over intrinsic motivation in SIM, b) defining two dimensions of extrinsic motivation, which are b1) external partners’ requirements and the potential benefits/rewards of compliance & b2) internal benefits of the company when measuring impact; c) concluding that more intrinsic motivations are in creating impact than in measuring impact; d) concluding that emotions, an element of intrinsic motivation, are found in the mixed-motive (balanced) model of social enterprise. Second, the thesis contributes to the literature on the challenges of social enterprises in SIM by synthesizing and providing alternative views with Molecke & Pinkse's (2017) model of delegitimization. In detail, the contributions are: a) highlighting three shared common challenges of SEs in Vietnam and the international context, b) eliminating the “SIM is irrelevant” friction and denying the delegitimization of formal SIM methods, c) proposing the alternative model to explain the use of bricolage approach: reasons for the bricolage approach do not come from the delegitimization of formal methods but from challenges in the resource-constraint context & motivations of the social entrepreneurs to do and improve the SIM practice. Third, this study advances the bricolage approach through a) identifying resource bricolage in SIM with two dimensions (level of effort including internal and external bricolage) beside level of creativity including material and ideational bricolage; b) synthesizing challenges in SIM with the type of bricolage used to overcome each challenge; c) showing the difference of three SE models in using resource bricolage; d) proposing the relationship between intrinsic/extrinsic motivations and the level of resource bricolage in SIM: while intrinsic motivation leads to the use of internal bricolage, extrinsic motivations stimulate the mobilizing external bricolage.
Keywords: social impact measurement; social enterprise; bricolage; motivation; challenges; social entrepreneurship